Prevention and Management of Employee Mental Health Issues in Finnish Multinational Corporations : Exploring HRM Approaches. - Ylimartimo, Iida (My University, 2024)
The significance of mental health in organizations is being increasingly addressed, but there is a lack of depth. Human resource management (HRM) practices related to mental health issues are usually more reactive than proactive. There is a gap in understanding organizational strategies from the experiences of the employees in Finnish multinational corporations. This thesis examines the role of HRM in addressing mental health issues in Finnish multinational corporations (MNCs) from an employee perspective. The aim of the study is to close the gap by researching how HRM approaches can be adapted to increasingly prevent and manage employee mental health challenges and better employee well-being. With Job Demand-Resources (JD-R) model and Ability, Motivation, and Opportunity (AMO) model, the research examines employee well-being. To see what effect demands, resources, and opportunities have on employees. Through qualitative research, the thesis provides an employee perspective within Finnish MNCs on the effectiveness of HRM practices. This was done by semi-structured interviews with ten employees of five different Finnish MNCs. The results of the research reveal that there are mental health preventive practices in place, such as flexible working arrangements and wellness programs, but their effectiveness in limited due to barriers such as stigma. Adapted JD-R and AMO models are used to illustrate the results. They reveal that high job demands with underutilized resources results in employee strain. They also show that providing employees with opportunities such as autonomy and feedback, motivation and engagement are fostered. The results of the study suggest that implementing more proactive approaches in HRM, such as continuous managerial training and regular mental health check-ins, are a necessity for better employee support. The research contributes to the field by emphasizing the importance of mental health tailored HRM strategies to increase employee well-being. It also provides insight from the employees themselves, on how the state of their mental health and performance can be in-creased, and by this leading to better organizational results for Finnish MNCs.
Keywords: mental health; employees; mental well-being; human resource management; international corporations; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business